2014
DOI: 10.1179/1743676114y.0000000208
|View full text |Cite
|
Sign up to set email alerts
|

Role of CaF2on mechanochemically synthesized leucite as dental veneering glass ceramics

Abstract: Leucite based glass ceramic is widely used in dental ceramics as porcelain fused to metals for veneering applications. Main properties considered here are high coefficient of thermal expansion and good mechanical properties. Owing to these requirements, high expansion phase such as leucite is incorporated in these glass ceramics. The present work was aimed to synthesise leucite using its stoichiometric batch compositions and subsequent high energy ball milling. CaF 2 was also added in another mix to study its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Zhang et al reported that the formation of kalsilite is a transitional stage that leads to crystallization of leucite. In addition, other recent studies are consistent with the view that kalsilite is the precursor of leucite . Moreover, in some studies, it is indicated that the prolonged heat treatment of natural or synthesized kalsilite at elevated temperatures will gradually lead to a complete conversion to leucite and this phenomenon is believed to relate to the high volatility of potassium …”
Section: Introductionsupporting
confidence: 65%
“…Zhang et al reported that the formation of kalsilite is a transitional stage that leads to crystallization of leucite. In addition, other recent studies are consistent with the view that kalsilite is the precursor of leucite . Moreover, in some studies, it is indicated that the prolonged heat treatment of natural or synthesized kalsilite at elevated temperatures will gradually lead to a complete conversion to leucite and this phenomenon is believed to relate to the high volatility of potassium …”
Section: Introductionsupporting
confidence: 65%
“…The mechanism in which CaF 2 acts is explained in Section . The eutectoid formed after CaF 2 incorporation contributed to the phase transformation from kalsilite to leucite . In Figure , CaF 2 has not been included in composition.…”
Section: Resultsmentioning
confidence: 99%
“…Ltd., Mumbai, India) were weighed in a stoichiometric ratio of leucite. This mixture was pulverized for 6 h in a high-energy planetary ball mill and subsequently fired at 1100 1C as discussed in our previous work [18]. Commercial Bioglass s 45S5 was prepared on a lab scale using traditional melt-quenching in a platinum crucible at 1400 1C.…”
Section: Preparation Of Leucite Bioglass and Ltfmentioning
confidence: 99%
“…This work also reports preparation of bioglass and low temperature frit (LTF) by traditional melt-quenching method [17,18]. Above three materials were mixed in an optimum ratio to form a composite with desirable properties.…”
Section: Introductionmentioning
confidence: 99%